Levels of physical activity and psychological well-being in non-athletes and martial art athletes during the COVID-19 pandemic - Monterrosa Quintero, A.; Echeverri Rios, A. R.; Fuentes-Garcia, J. P.; Gonzalez Sanchez, J. C. (International Journal of Environmental Research and Public Health, 2022)
Background: The objectives of this study were to identify which of the sociodemographic variables affected psychological well-being in two populations that differed in their sports practice at the end of the COVID-19 lockdown in Colombia. Methods: The study was conducted through an online survey using the IPAQ-S and PGWBI-S questionnaires six months after the first SARS-CoV-2 lockdown, between 8 and 22 September 2020 in Colombia. The total number of study participants was 582, subdivided into two groups: (i) non-athlete university population (NA) without constant practice in physical activity or sports training (n = 470); and (ii) martial arts athletes (n = 122) with a sports career (A), 7.4 ± 3.4 years of experience, at different levels (advanced belts and black belts). Results: Sports practice, normal BMI levels and high levels of physical activity translated into absence of distress (ND) in the psychological well-being of populations. The variance between the factors could be explained by the general health dimension (2.4% population; 4.2% sex; 12% physical activity; 2.6% age). A moderate correlation between vitality and MET was found (r = 0.33; p < 0.001). Conclusions: The practice of a sport such as martial arts, normal body mass index and high levels of physical activity were factors that positively reduced levels of distress, translated into better psychological well-being in populations, and the general health dimension presented important contributions to psychological well-being. Intervention plans must be carried out, especially in populations that do not practice physical activity—mainly female and those under 40 years of age.